Low‐Angle Normal Faults on the NW Shelf of Australia: Implications for Late Paleozoic Rifting. Issue 6 (22nd June 2022) - Deng, Hongdan; McClay, Ken; Belgarde, Catherine
Abstract: Late Paleozoic rifting of the NW Shelf of Australia formed a wide basin that fundamentally controlled the Mesozoic continental rifting and passive margin development; however, structural style associated with this extensional process remains poorly constrained. Here, we integrate high‐resolution seismic data with well data from the proximal domain of the NW Shelf to show that the Mermaid fault system in the eastern Dampier Sub‐basin is a large‐scale (∼80 km long), low‐angle (5–20°) normal fault with up to 10 km offset formed during the Late Paleozoic rifting. In its northern and southern domains, the Mermaid fault has a planar geometry with characteristic extensional structures. In its central domain, seaward‐dipping, domino‐style normal faults in the upper crust extend downward into a highly reflective seismic zone that arches upward to form an elliptical dome. Growth strata in the hangingwall half‐graben and footwall basement reflections indicate that the Mermaid fault initiated as a high‐angle normal fault and was rotated by footwall exhumation during extension. Intrabasement deformation along and below the Mermaid fault is characterized by moderate‐ to high‐amplitude, semi‐continuous seismic reflectors that are distinct from transparent reflection character in the overlying basement unit. Comparison of the Mermaid fault system to well‐studied detachment faults in metamorphic core complex settings reveals striking similarities. We therefore suggest that the Mermaid fault developed as part of a nascent metamorphic core complex with a warm to hot footwall that enabled middle‐lower crustal flow during the Late Paleozoic continental rifting, likely induced by southward subduction of the Paleo‐Tethys Ocean. Key Points: The Mermaid fault is a low‐angle normal fault with "ramp‐flat" geometry that developed through footwall exhumation of deep crust material A series of domino‐style high‐angle faults passing downward into an arched ductile zone that resembles a nascent metamorphic core complex Continental rifting occurred in association with subduction of the Paleo‐Tethys that introduced heat and magmatism to the extended rift area